Ageism as Portrayed in the Intern (2015): A Systemic Functional Multimodal Discourse Analysis - Haqikoh Ukhrowiyah (Fakultas Ilmu Budaya, 2025)
This research was conducted using qualitative methods to analyse verbal (dialogues) and visual (scenes) data. The data were analysed using transitivity and mood analysis for linguistic aspects, as well as representational, interactive, and compositional meaning for visual aspects. This research classifies the data into three categories of Ageism based on Butler's theory: prejudice, discriminatory attitudes, and institutional policies, and then interpreted comprehensively. Based on the analysis of eight scene excerpts. The transitivity results show that material processes are most dominant, followed by relational and mental processes, indicating a focus on concrete actions and identity. The most dominant mood is declarative, signalling informative and expressive communication. Visual analysis shows that all scenes use narrative and gaze offer processes, with close shots and eye-level shots emphasising social proximity and equality. Compositionally, character placement, salience and framing were used to direct attention and display interpersonal relationships and ideological structures in the scenes. All results are associated with forms of Ageism such as belittling attitudes between the younger characters to the elderly, doubting the abilities of the elderly, and social marginalisation. Based on the analysis, this study concludes that The Intern explicitly and implicitly portrays Ageism through language and visuals. Linguistically, an elderly character like Ben is often the object of questions or scepticism, while visually, he is depicted in a marginal or separate position, especially at the beginning of the film. However, as the narrative develops, the relationship between characters shows a shift in values, from discrimination to acceptance. The findings confirm that Ageism does not only emerge in direct interactions, but is also shaped by social structures and media visuals. This research suggests that the media should be more conscious of the representation of age groups and avoid reinforcing negative stereotypes of the elderly.
Reuploud file repositori 29 Jan 2026_Yudi
Keywords: Ageism; The Intern (2015): A Systemic Functional Discourse Analysis